Generation of Marker-Free Transgenic Rice Resistant to Rice Blast Disease Using Ac/Ds Transposon-Mediated Transgene Reintegration System - Li, Xin; Pan, Longyu; Bi, Dongling; Tian, Xudan; Li, Lihua; Xu, Zhaomeng; Wang, Lanlan; Zou, Xiaowei; Gao, Xiaoqing; Yang, Haihe; Qu, Haiyan; Zhao, Xiangqian; et al. (Frontiers in Plant Science, 2021)
Rice blast is one of the most serious diseases of rice and a major threat to rice production. Breeding disease-resistant rice is one of the most economical, safe, and effective measures for the control of rice blast. As a complement to traditional crop breeding, the transgenic method can avoid the time-consuming process of crosses and multi-generation selection. In this study, maize (Zea mays) Activator (Ac)/Dissociation (Ds) transposon vectors carrying green fluorescent protein (GFP) and red fluorescent protein (mCherry) genetic markers were used for generating marker-free transgenic rice. Double fluorescent protein-aided counterselection against the presence of T-DNA was performed together with polymerase chain reaction (PCR)-based positive selection for the gene of interest (GOI) to screen marker-free progeny. We cloned an RNAi expression cassette of the rice Pi21 gene that negatively regulates resistance to rice blast as a GOI into the Ds element in the Ac/Ds vector and obtained marker-free T1 rice plants from 13 independent transgenic lines. Marker-free and Ds/GOI-homozygous rice lines were verified by PCR and Southern hybridization analysis to be completely free of transgenic markers and T-DNA sequences. qRT-PCR analysis and rice blast disease inoculation confirmed that the marker-free transgenic rice lines exhibited decreased Pi21 expression levels and increased resistance to rice blast. TAIL-PCR results showed that the Ds (Pi21-RNAi) transgenes in two rice lines were reintegrated in intergenic regions in the rice genome. The Ac/Ds vector with dual fluorescent protein markers offers more reliable screening of marker-free transgenic progeny and can be utilized in the transgenic breeding of rice disease resistance and other agronomic traits.